Indonesian Education Digitalization Collaboration Program For Madrasah Through The World Bank and The Ministry Of Religion - Kusuma, Raden Ahmad Naufal Pranata; Widyarsa, Mohammad Riza (Paedagogia: Jurnal Pendidikan, 2024)
The education digitalization program in madrasah throughout Indonesia is an initiative to overcome significant challenges in improving the quality and access to education, especially in underserved areas. The program seeks to create a more equitable educational landscape by leveraging digital technology, allowing students and educators to benefit from modern learning tools and resources. The theoretical framework guiding this research emphasizes the importance of knowledge transfer and best practices from digital education models successfully implemented in other countries. A qualitative approach analyses implementation strategies, challenges, and program outcomes. The findings show that while these initiatives have great potential to transform education, they also face obstacles such as limited infrastructure and the need for comprehensive training for educators. Ultimately, the study concludes that ongoing commitment and collaboration among stakeholders are essential to realizing the full benefits of digital education in Indonesian madrasah.